2015
DOI: 10.1007/s10653-015-9787-8
|View full text |Cite
|
Sign up to set email alerts
|

HCHs and DDTs in Yellow River of Henan section—a typical agricultural area in China: levels, distributions and risks

Abstract: The levels, potential sources and ecological risks of hexachlorocyclohexanes (HCHs) and dichlorodiphenyltrichloroethanes (DDTs) in Yellow River of Henan section, a typical agricultural area in China, were investigated. Surface water samples and suspended particulate matters (SPMs) were collected from 23 sites during two seasons. In wet season, the residues of ∑HCHs (α-HCH, β-HCH, γ-HCH and δ-HCH) and ∑DDTs (p,p'-DDT, o,p'-DDT, p,p'-DDE, p,p'-DDD) ranged from 41.7 to 290 and 4.42 to 269 ng/L in surface water, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 41 publications
0
3
1
Order By: Relevance
“…The BHCs were also detected in all sites with concentrations of 13.6 ± 2.88 to 21.0 ± 2.83 ng/L (Table ). These concentrations were slightly higher than previous data in the Pearl River (0.21–5.12 ng/L) , but in the similar range of BHC concentrations in other rivers in China (1.10–290 ng/L) .…”
Section: Resultscontrasting
confidence: 54%
“…The BHCs were also detected in all sites with concentrations of 13.6 ± 2.88 to 21.0 ± 2.83 ng/L (Table ). These concentrations were slightly higher than previous data in the Pearl River (0.21–5.12 ng/L) , but in the similar range of BHC concentrations in other rivers in China (1.10–290 ng/L) .…”
Section: Resultscontrasting
confidence: 54%
“…Total DDTs in a typical agricultural area of China range from 0.00442 to 0.269 ng/mL in surface water [42]. Feng et al, 2013 reported DDT levels in the range of 0.2 to 9.3 ng/mL in the water of the Yangtze River Delta, China, which is used for rice production [43].…”
Section: Discussionmentioning
confidence: 99%
“…However, in the seventies, most of the countries banned its use due to its toxicity 24 . Currently, in humans, a large percentage of DDT has already been transformed into its metabolite DDE (1,1′-(2,2-dichloroethene-1,1-diyl)bis(4-chlorobenzene)) 25,26 , but DDT still prevails in samples from the environment 25,27 . Moreover, some countries still use DDT as a pesticide in the fight against malaria 28 .…”
Section: Introductionmentioning
confidence: 99%